Optimal Public Transport Pricing: Towards an Agent-based Marginal Social Cost Approach. (1st April 2015) - Kaddoura, Ihab; Kickhöfer, Benjamin; Neumann, Andreas; Tirachini, Alejandro
In this paper, marginal cost-pricing rules are applied to an agent-based model. User-specific optimal bus fares are estimated by simulating user interactions at a microscopic level. We consider external effects of prolonged in-vehicle and waiting times (including the effect of full buses on boarding denials) induced by passengers boarding vehicles. We give a new-look to the relationship between optimal fare and travel distance, which is found to depend crucially on the type of external cost that is considered when calculating fares. Conditions for optimal bus fares that increase or decrease as a function of trip length are numerically found.